Tourism destination attributes: what the non-visitors say - higher education students' perceptions - Shanka, Tekle; Phau, Ian (Routledge, 2008)
The paper presents a study on tourists’ consumption values and perceived beneficial image of the tourist destination, Mauritius. Specifically, the two innovations of the study are, first, that the target market is university student travellers and, second, the respondents have no previous travel experience to the tourist destination. Independent sample t-tests and one-way analysis of variance tests indicated a number of statistically significant differences of value components (from established scales) across demographics. In general, Mauritius emerged to command a very favourable perception as a tourist destination for student travellers. Several managerial and theoretical implications are discussed, with suggestions for future directions.